Neurothrombectomy trial results: stroke systems, not just devices, make the difference. Issue 7 (October 2015) - Mocco, J.; Fargen, Kyle M.; Goyal, Mayank; Levy, Elad I.; Mitchell, Peter J.; Campbell, Bruce C. V.; Majoie, Charles B. L. M.; Dippel, Diederik W. J.; Khatri, Pooja; Hill, Michael D.; Saver, Jeffery L.
<x xml:space="preserve">Abstract</x> The overwhelming benefit demonstrated in the four recent randomized trials comparing intra‐arterial therapies to medical management alone will have a transformative effect on the emergent management of strokes throughout the world. New generation neurothrombectomy devices were critical to trial success, but not the sole driver of patient outcomes in these trials. Patients in the positive trials were treated at hospitals with complex, efficient, resource‐rich, team‐based stroke systems in place. To ensure attainment of trial results in actual practice, patients should receive treatment at facilities certified as having the resources, personnel, organization, and continuous quality improvement processes characteristic of trial centers. It is our hope that, through greater education initiatives, robust resource investment, and developing quality‐based certification processes, the results demonstrated by these trials may be extrapolated to greater numbers of centers – in turn allowing greater access for patients to high‐quality, advanced stroke care.